0260 Shifting Late- And Short-sleeping Teens Earlier. (12th April 2019) - Crowley, Stephanie J; Smith, Amelia E; Velez, Sabrina L; Eastman, Charmane I
Abstract: Introduction: A large majority of adolescents go to bed too late to get sufficient (>8h) school-night sleep; this is partly driven by delayed circadian clocks. In this ongoing study, we are testing whether one weekend of morning bright light and a gradual advance of school-night bedtimes can advance the circadian system and increase sleep duration in high school students. Methods: So far, 32 adolescents (14.6-17.9 years; 16 females) with self-reported short school-night sleep (≤ 7h) and late bedtimes (school-night average ≥ 23:00; non-school average ≥ midnight) completed a 31-day protocol during the school year. After a 2-week baseline of usual sleep at home, participants live in the laboratory for a weekend, during which the dim light melatonin onset (DLMO) is measured. For the next two weeks, the intervention group (n=15) is instructed to advance school-night bedtime from their own baseline: 1h earlier during the first week and 2h earlier in the second week. Wake times remain unchanged. During the intervening weekend, intervention participants receive bright light in the lab on both weekend mornings (~6000 lux; 2.5 h intermittent light) and 8.5-h sleep opportunities each night. A control group (n=17) is given no instruction about bedtimes and does not attend the bright light weekend. DLMO is measured during the final (third) weekend in all participants. Actigraphic sleep is collected throughout. Results: Intervention DLMOs are advancing more than controls (50.4±49.8 mins vs. -7.2±49.2 mins; t(30)=3.3, p=.003). By the final weekend, about half (n=8) of the intervention group have DLMOs > 9.5h before their school-day wake time (early enough to facilitate sufficient sleep). The intervention group is increasing total sleep time by 68 mins by falling asleep 89 mins earlier than baseline. The control group shows no changes in sleep duration nor fall asleep time. Conclusion: These data suggest that one weekend of morning bright light plus earlier school-night bedtimes can advance circadian phase and increase sleep time. Variability in responses, however, suggests that some adolescents need to phase advance more to be aligned with early school start times. Support (If Any): R01 HL105395 (S.J.C.)